The Role of SWOT Analysis of the Potency for Establishing a Micro Waqf Bank in East Kotawaringin Regency - Zulkifli Zulkifli; Muhammad Noor Sayuti; Fadiah Adlina; Anisa Anisa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the strengths, weaknesses, opportunities, and threats to the efforts to establish MWB in East Kotawaringin Regency. This study analyzed the strengths, weaknesses, opportunities, and threats to efforts to establish MWB in East Kotawaringin Regency. This research used a qualitative method with a descriptive approach. Collecting data using observation, interviews, and documentation was processed using Fred's SWOT analysis technique R. David. The results showed through a SWOT analysis that the strategic position of the potential for the establishment of a Micro Waqf Bank in East Kotawaringin Regency, which is located in quadrant II from the internal side, has strength with the existence of a business unit managed by Islamic boarding schools. Still, from external factors, there are threats, namely low Islamic financial literacy. The strategy must be applied to use strengths to take advantage of opportunities. Among the Islamic boarding schools in East Kotawaringin Regency, Pondok Pesantren of Sabilal Muhtadin has the most potential for establishing a Micro Waqf Bank. This is based on Pondok Pesantren of Sabilal Muhtadin having a cooperative business unit already a legal entity. A sizeable socioeconomic impact on the Islamic boarding school community and has implemented one of the strategies to increase Islamic financial literacy.